PEMBERDAYAAN SDM UMKM GULA JAWA MELALUI GREEN MARKETING DAN INOVASI PACKAGING BERBASIS LINGKUNGAN - Ratna Agustina; Mokhamad Tohari Ilyas; Muhammad Ilham Firmansyah (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
This community service program aimed to empower the human resources of palm sugar SMEs in Magelang through the implementation of green marketing strategies and environmentally based packaging innovation. The main challenges faced by the partners included limited understanding of environmentally friendly marketing, lack of packaging innovation, and low product competitiveness in broader markets. The methods employed consisted of training sessions, mentoring activities, and hands-on practice in designing eco-friendly packaging as well as developing promotional strategies based on sustainability values. The results indicated an improvement in the knowledge and skills of SME actors in applying green marketing concepts, along with the creation of more attractive, informative, and environmentally friendly packaging designs. These innovations contributed to enhancing the product image and expanding market opportunities. Overall, the program strengthened the competitiveness of palm sugar SMEs while promoting sustainable business practices aligned with environmental conservation principles.